National Board-certified Teachers: Can They Make a Difference in Maine Schools? - Mackenzie, Sarah; Harris, Walter (Maine Policy Review, 2008)
The National Board for Professional Teaching Standards (NBPTS) was created in an effort to improve the status of teaching as a career. In 2006, the Maine legislature authorized a salary supplement for Maine teachers who were certified by the NBPTS. Sarah Mackenzie and Walter Harris describe their study focused on the value of NBPTS certification in professional development and teacher leadership; teacher motivation for seeking certification; barriers to certification; and how Maine teachers might be encouraged to seek certification. They point out that National Board certification is one among many ways to support and improve the quality of teaching in Maine.
Keywords: Maine; teacher certification; national teacher certification